UJI KADAR VITAMIN C DAN AKTIVITAS ANTIOKSIDAN DARI FRAKSI KULIT BUAH MELINJO (Gnetum gnemon L) - Ibrahim, Kevvy Buana; Wardana, Fendi Yoga; Prasetiyo, Bagus Dadang; Puspitasari, Meyrika Dwi (Poltekkes Kemenkes Bandung, 2024)
Melinjo (Gnetum gnemon L) in Indonesia is widely used as a food ingredient but melinjo fruit peel is considered waste because there has been no effort to maximize its utilization and there has been no research details of the active compound content in it. Melinjo fruit peels are thought to have the potential to be a source of vitamin C and natural antioxidants that can suppress the activity of free radicals. The study aimed to determine the vitamin C content and antioxidant activity of melinjo fruit peel fraction. It was conducted from August to September 2023 at the Pharmacognosy and Chemistry Laboratory of ITSK RS DR. Soepraoen. Extraction using maceration method followed fractionation. Determination of vitamin C content using UV-Vis spectrophotometry, while determination of antioxidant activity using the DPPH method. The highest vitamin C content was 7.3483 μg/mL in ethanol fraction, followed by ethyl acetate 7.0285 μg/mL and n-hexane 3.6108 μg/mL. Antioxidant activity results with the highest IC50 value of 279.35 μg/mL in ethyl acetate fraction, followed by ethanol 333.98 μg/mL, and n-hexan 4077.31 μg/mL. Solvents with higher polarity can extract vitamin C compounds from simplisia more efficiently and semi-polar solvents can more effectively attract compounds that have antioxidant activity, the type of polarity of a solvent can affect the number and type of compounds to be extracted according to the polarity of compound. It is recommended that further research test the antioxidant active compounds of ethyl acetate fraction and other methods of testing the antioxidant activity melinjo fruit peel.